National situation COVID-19 Costa Rica: an open source implementation for online map visualization - Céspedes-Vindas, Adriana (2022)
Geographic analysis tools have been used by the health sector for sanitary policy, epidemiological, surveillance and health promotion purposes. In order to track the COVID-19 pandemic, the Ministry of Health and the Technological Research and Innovation Laboratory (LIIT-UNED) of Costa Rica, launched a technological solution using open source software. The resulting web tool monitors the epidemiological behavior of the virus on a daily basis. The solution also serves to communicate epidemiological information of the virus to the general population. From April to September 2020, more than 200,000 people in more than 119 countries accessed the website.  In this paper, we present the considerations of design, the workflows that followed for the implementation of the website, as well as a discussion of the type of Open Source solutions for working with geographic information systems in health.